Analysis of the Relationship Between Middle-Level Manager's Transformational Leadership Style and the Implementation of Safety Culture with Employee Job Satisfaction: Case Study - Nurul Maulina Aladin; Rima Semiarty; Yahya Marpaung (Newinera Publisher, 2025)
Job satisfaction is basically about what makes someone happy in their job. Factors that affect job satisfaction include cultural factors and organizational factors. leadership style is one that supports the achievement of employee job satisfaction. With an effective leadership style, it will be able to foster a good safety culture and can increase employee job satisfaction. RSUD Prof. H. Muhammad Yamin, SH is one of the hospitals owned by the government of West Sumatra Province located in the city of Pariaman. This study used a mixed-method method with a sequential explanatory approach to 110 employee respondents and research informants determined by simple random sampling and purposive sampling techniques. Data collection was obtained from questionnaires, in-depth interviews, observation, and document review. The data analysis used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that there was a significant relationship between leadership style and safety culture, as well as safety culture on job satisfaction with p values of 0.000 and 0.000, respectively. Meanwhile, leadership style is not related to job satisfaction with a p value> 0.05. Leadership style has a relationship with job satisfaction through the mediating variable of safety culture with a p value of 0.000. Other factors that influence employee job satisfaction at Prof. H. Muhammad Yamin Hospital, SH are social factors, environmental factors, and financial factors. There is a relationship between leadership style and employee job satisfaction through the mediation of safety culture.